2018
DOI: 10.3390/ani8110190
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pet Cats: The Impact of the Cat Tracker Citizen Science Project in South Australia

Abstract: Simple SummaryDomestic cats are popular pets worldwide and play an important role in the lives of many of their owners; however, there is growing awareness of the potential negative impacts of cats. The Cat Tracker citizen science project was conducted in South Australia to better understand domestic cats, their movement, and related community views. The project was deliberately designed to engage cat owners and assist them to make informed decisions about the management of their pet cats. The project collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 34 publications
5
35
0
Order By: Relevance
“…Owner contact details from microchip registration were used to locate the owners. This wandering behavior of owned cats is consistent with GPS tracking data for South Australian pet cats, where the average daytime range was 1 hectare, and 2 hectares at night [ 32 ]. It is also consistent with research demonstrating that 75% of lost cats when found were located within 500 m of their home [ 33 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Owner contact details from microchip registration were used to locate the owners. This wandering behavior of owned cats is consistent with GPS tracking data for South Australian pet cats, where the average daytime range was 1 hectare, and 2 hectares at night [ 32 ]. It is also consistent with research demonstrating that 75% of lost cats when found were located within 500 m of their home [ 33 ].…”
Section: Discussionsupporting
confidence: 81%
“…The applicability of our findings outside the limited and defined range of a university campus or similar site is unclear. Immigration might constitute a larger component where colonies are immediately adjacent to houses with free-roaming owned cats, given the limited range of most pet cats [ 32 ]. Furthermore, in common with many previous reports of TNR programs, no control group was included to document and compare changes in cat numbers in an unmanaged population.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies have demonstrated the usefulness of CS projects for scientific research and have also shown that CS provides other socio-ecological outcomes (Shirk et al, 2012;McKinley et al, 2017). For example, participating in CS projects enhances people's knowledge about wildlife (Brossard et al, 2005) or about science , and even induces changes in environmental management (Danielsen et al, 2005(Danielsen et al, , 2010. Also, changes in people's attitudes toward science or the environment have been demonstrated (Price and Lee, 2013), but are not widely investigated (Brossard et al, 2005).…”
Section: Importance Of Public Preferences For Participation In Citizementioning
confidence: 99%
“…For example, participating in CS projects enhances people's knowledge about wildlife (Brossard et al, 2005) or about science , and even induces changes in environmental management (Danielsen et al, 2005(Danielsen et al, , 2010. Also, changes in people's attitudes toward science or the environment have been demonstrated (Price and Lee, 2013), but are not widely investigated (Brossard et al, 2005). One socio-ecological outcome considered important in conservation practice is to engage communities in actions to mitigate environmental problems (McKinley et al, 2015).…”
Section: Importance Of Public Preferences For Participation In Citizementioning
confidence: 99%
“…The development of low-cost Global Positioning System (GPS) technology increasingly used by the public might change this scenario. The most prominent citizen science study making use of GPS technology is the Cat Tracker study with pet cats in Australia [17]. However, even though sustainable grazing management begins with a profound knowledge of the grazing behaviour, no studies investigating livestock behaviour with a citizen science approach have been carried out yet.…”
Section: Introductionmentioning
confidence: 99%